Functional Studies on Novel RET Mutations and Their Implications for Genetic Counseling for Hirschsprung Disease - Wang, Hui; Li, Qi; Zhang, Zhen; Xiao, Ping; Li, Long; Jiang, Qian (Frontiers in Genetics, 2019)
Hirschsprung disease (HSCR) is a genetic disorder characterized by the absence of ganglion cells in the gut. RET is considered to be the main susceptibility gene. In our previous screening of 83 HSCR patients, targeted exome sequencing identified nine rare variants of RET, most of which were new discoveries. Here, we performed in vitro arrays with functional studies to investigate their effects. Two variants (p.R77C and p.R67insL) were demonstrated to disrupt the glycosylation of RET and affect its subcellular localization. Three nonsense mutations (p.W85X, p.E252X, and p.Y263X) could not produce detectable RET full-length protein, and the other three mutations (p.R770X, p.Q860X and p.V778Afs*1) were translated into truncated proteins of predicted sizes. One canonical splice acceptor site mutation (c.2802-2 A>G) was verified to affect gene regulation through aberrant splicing. In addition, we explored the effects of read-through reagents on RET nonsense mutations and showed that G418 significantly increased the full-length RET protein expression of p.Y263X in a dose-dependent manner, together with a mild recovery of p-ERK and p-STAT3. Our data provide a functional analysis of novel RET mutations and suggest that all of the rare variants detected from patients with clinically severe HSCR are indeed pathogenic. Thus, our findings have implications for proper genetic counseling.